Torneamento do aço inoxidável supermartensítica sob lubri-refrigeração com baixa e alta pressões - Deibe Valgas dos Santos (2019)
The chemical and petrochemical industries continually invest in new technologies and materials. Tubes used in the extraction of oil and natural gas in pre-salt layer must be able to withstand extremely aggressive environments, with high concentrations of CO2 and H2S. Such applications require the employment of supermartensitic stainless steels with high corrosion resistance and toughness. The aim of the present work is to identify the main factors influencing the machinability of Super Chrome 13 stainless steel (grade CA6NM, according to ASTM A743) when turning using different cutting speeds, cooling methods (low and high pressure of 0,1 and 80 bar, respectively) and PVD and CVD coated carbide inserts of different grades. Microstructure, chemical composition, mechanical properties, roughness of the workpiece, chips morphology, tool life and wear, turning force components, induced residual stress, strain, strain rate, normal and shear stress at the shear plane were evaluated. The results indicated a martensitic microstructure with the presence of Ti,which increases the abrasiveness of the work material. This presented a yield stress of 738.7 MPa and the tensile stress of 794.7 MPa. Cutting insert grade, cooling method and cutting speeds did not present a significant influence on the roughness. With regard to tool life and wear, it was noticed that insert grade MC 7015 presented better performance. Dry cut combined with the highest cutting speed plus the MC 7015 insert provided the lowest machining force values. When cooling under high pressure, connected arc chips were produced, irrespectively of cutting speeds and insert grade. Dry cutting associated promoted the lowest value for deformation and deformation rate and shear stress of the material. Finally, the lowest shear stress value was obtained when dry turning at the cutting speed of 150 m/min.